1982
DOI: 10.1038/ki.1982.168
|View full text |Cite
|
Sign up to set email alerts
|

Importance of dietary sodium in the hypercalciuria syndrome

Abstract: Daily urinary calcium excretion in renal stone-forming subjects is shown to vary directly with moderate changes in dietary sodium intake. The changes produced are sufficient to alter the basic diagnostic classification from 'hypercalciuric' to 'normocalciuric' because dietary sodium is reduced from 200 to 80 mM/day. Similar changes were observed in fasting morning 'spot' urine samples, resulting in alteration of diagnostic subclassification between so-called 'absorptive' and 'renal' categories, in the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2
9

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(87 citation statements)
references
References 16 publications
3
73
2
9
Order By: Relevance
“…As expected from previous reports, (38,39) we observed a positive relation between sodium intake (as determined by 24-h urinary sodium) and urinary calcium excretion. Because the associations between urinary sodium and urinary calcium in our study were similar in individuals with and without a history of kidney stones, our results are not consistent with the hypothesis that SF have an exaggerated calciuric response to sodium (40).…”
Section: Discussionsupporting
confidence: 78%
“…As expected from previous reports, (38,39) we observed a positive relation between sodium intake (as determined by 24-h urinary sodium) and urinary calcium excretion. Because the associations between urinary sodium and urinary calcium in our study were similar in individuals with and without a history of kidney stones, our results are not consistent with the hypothesis that SF have an exaggerated calciuric response to sodium (40).…”
Section: Discussionsupporting
confidence: 78%
“…Since this relationship results from an effect of sodium on calcium [1], a reduction in salt intake is potentially a useful method for controlling hypercalciuria in stone-formers. Muldowney et al [13] demonstrated clearly in the early 1980s how closely urinary calcium followed salt intake and urinary sodium excretion, so that the definition of "idiopathic" hypercalciuria would be meaningless without allowing for the concurrent sodium intake. More recently, clinical anecdotes have strongly supported the view that a moderate reduction in salt intake could play a very important clinical role in reducing urinary calcium excretion, blood pressure and the recurrence of kidney stones in hypertensive patients suffering from recurrent urolithiasis [14].…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent 9-month period of sodium restriction (by only 30 mmol/day) in a sub-sample failed to reveal any change in bone mineral density. A high sodium intake is also implicated in the pathogenesis and treatment of hypercalciuria in both children and adults [100][101][102] and of calcium depletion in corticosteroid treated patients. 103 Normal rats given salt supplements also have an increase in urinary calcium excretion, and after a year their bones contain less calcium than their controls.…”
Section: Bone Density and Renal Stonesmentioning
confidence: 99%